2010
DOI: 10.1099/mic.0.027144-0
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and translocation signals and DspB/F-binding domains in the type III effector DspA/E of Erwinia amylovora

Abstract: DspA/E is a type III effector of Erwinia amylovora, the bacterial pathogen that causes fire blight disease in roseaceous plants. This effector is indispensable for disease development, and it is translocated into plant cells. A DspA/E-specific chaperone, DspB/F, is necessary for DspA/E secretion and possibly for its translocation. In this work, DspB/F-binding sites and secretion and translocation signals in the DspA/E protein were determined. Based on yeast two-hybrid assays, DspB/F was found to bind DspA/E wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…These contradictory results indicate that the requirement for the DspB/F chaperone is influenced by the Cterminal part of the protein. In accordance with this, it was found that DspB/F also interacts with the C-terminal half of DspA/E (80).…”
Section: Current Understanding Of Fire Blight Host-pathogen Interactionssupporting
confidence: 62%
See 3 more Smart Citations
“…These contradictory results indicate that the requirement for the DspB/F chaperone is influenced by the Cterminal part of the protein. In accordance with this, it was found that DspB/F also interacts with the C-terminal half of DspA/E (80).…”
Section: Current Understanding Of Fire Blight Host-pathogen Interactionssupporting
confidence: 62%
“…Structural modeling of DspB/F and identification of candidate DspB/F residues involved in virulence and DspA/E interaction confirm that DspB/F functions as a classical T3SS chaperone (115). Neither disruption of the N-terminal DspA/E chaperonebinding domain nor deletion of the dspB/F gene had a significant impact on translocation levels of N-terminal DspA/E-CyaA fusions (114), but the presence of DspB/F strongly enhances the translocation of a DspA/E-AvrRpt2 fusion protein into plant cells (80). These contradictory results indicate that the requirement for the DspB/F chaperone is influenced by the Cterminal part of the protein.…”
Section: Current Understanding Of Fire Blight Host-pathogen Interactionsmentioning
confidence: 55%
See 2 more Smart Citations
“…However, minimal transport signals as well as protein regions required for the HpaB-dependent translocation of XopA and HrpF have not yet been identified. To date, separate secretion and translocation signals have been described in effector proteins from the animal-pathogenic bacterium Yersinia and the plant pathogen Erwinia amylovora (69)(70)(71)(72). In the case of the Yersinia effector protein YopE, the secretion specificity is determined by the minimal secretion signal (73).…”
Section: Discussionmentioning
confidence: 99%